Головні етапи розбудови дендропарку “Олександрія” НАН України - Galkin, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
For the first time since 1917 provides reliable data on the making of the park Olexandria in the Bila Tserkva. Stylistic features, the structure and symbolism of park compositions are analysed. The main stages of development of the park are determined.